Money Matters Umgang mit Geld als soziale und kulturelle Praxis - Meyer, Silke (bricolage, 2014)
This volume examines ways of dealing with money as social and cultural forms. Empirical examples from the discipline of European Ethnology encompass modified bank notes, regional monies, Deutschmark-nostalgia, the role of pocket money in parenting, pawned money, money gifts and remittances. In all of them, money can be read as a means of social positioning, as a way of negotiating belonging, as biographical self-emancipation and as social inclusion and exclusion. The case studies share one aim: by deconstructing economic as social practices, the economy as such can be anthropologized (Paul Rabinow), i.e. stripped off its allegedly self-evident universal claim and revealed in its culturally, socially and historically specific functions.